Transition‐Metal‐Free Matsuda‐Heck Type Cross‐Coupling and Mechanistic Evidence for a Radical Mechanism. Issue 10 (23rd February 2021) - Bergès, Julien; Zaid, Yassir; Tlili, Anis; Sotiropoulos, Jean‐Marc; Taillefer, Marc
Abstract: The Matsuda‐Heck reaction, usually performed with palladium catalysts, can be carried out under transition‐metal‐free conditions in the presence of a KO t Bu/DMF couple. This system allows the selective and direct synthesis of stilbenes from aryldiazonium salts under mild temperature (20 °C). Mechanistic studies suggest a radical pathway in which the DMF acts as the initiator of the overall process. Abstract : The Matsuda‐Heck reaction is carried out under transition metal free conditions in the presence the KO t Bu/DMF system which allows, at 20 °C, the selective and direct synthesis of stilbenes from aryldiazonium salts. Mechanistic studies suggest an overall radical process.